The Effect of Work Involvement and Organizational Support on Employee Performance in the Company - Nabila Almira Hasibuan (Junal Ilmu Manajemen, 2021)
Effect of engagement and support organization of work the performance of employees in port of indonesia i Medan this study aims to determine the effect of job involvement and organizational support to employees performance in pt port of Indonesia i Medan. This research was conducted at PT Pelabuhan Indonesia i Medan. The study population was employees PT. port i Medan Indonesia totaling 261 people. The sample in this study amounted to 73 people by using simple random sampling method. This type of research is associative research. The data used are primary and secondary data. Primary data were collected through a questionnaire distributed to employees of PT Pelabuhan Indonesia I Medan, while secondary data obtained from the documentation obtained from various information owned by PT Pelabuhan Indonesia I Medan. The analytical method used is multiple linear regression analysis. The results based on multiple linear regression analysis showed that work engagement has the effect of 33.1% to the support organization at PT Pelabuhan Indonesia I Medan and 66.9% are influenced by factors other than job involvement and support organizations have an influence of 36.5%, and 63.5% are influenced by factors other than the support of the organization at PT Pelabuhan Indonesia I Medan. Partially (t test) indicates that the Employment Engagement has T_ (count (2.071)>) T_ (table (1.66), Support Organization has T_ (count (4.135)) F_table (9.447> 2.95) based on the hypothesis testing criteria H_a H_0 is accepted and rejected. Simultaneously (Test f) indicates that the involvement and support of organizations working simultaneously and significantly affects the performance of employees. Partially (t test) showed that work engagement had a positive and significant impact on employee performance and organizational support has positive and significant impact on the performance of employees of PT Pelabuhan Indonesia I Medan.